Faktor-Faktor yang Berhubungan dengan Burnout pada Perawat di Rumah Sakit Umum Kota Tangerang Selatan Tahun 2023 - Adinda Rizki Amalia; Munaya Fauziah (Muhammadiyah International Public Health and Medicine Proceeding, 2024)
The Ministry of Health data as of 4 January 2023, recorded there were 524.508 nurses. In addition, nurses also have high responsibilities, and job demands cause vulnerable nurses to burnout. To determine the factors associated with burnout among nurses in the public hospital city of Tangerang. This study used the method with a cross-sectional study design of 55 samples. Sampling is done using a stratified random sampling technique, then sample selection using the method of simple random sampler. Data collection is done using a questionnaire. The study was conducted using the Chi-square test. There was a relationship with burnout in nurses, as the level of education (p = 0,028), marriage status ( p = 0.000), working time (p=0,050), social support (p= 0,022), conflict (P = 0,000), disturbance of the community system in work (p > 0,012), and isolation (0,010). While gender (p = 0.686), and age (p=0,039) are not related to burnout in nurses. This study concludes that factors related to burnout in nurses are education levels, marital status, working time, social support, conflict, disturbance of community systems at work, and isolation. Meanwhile, gender and age are not associated with burnout in nurses.